How Does India's Rural Roads Program Affect the Grassroots? Findings from a Survey in Orissa - Bell, Clive; van Dillen, Susanne (World Bank, Washington, DC, 2012)
This paper analyzes the effects of all-weather rural roads on households' net output prices, education and health in a poor, drought-prone region of India. Of 30 villages originally surveyed in 2001-02, when two had such roads, a further nine received them between January 2007 and December 2009 under the program Pradhan Mantri Gram Sadak Yojana. Cross-section comparisons involving all villages and 'before and after' comparisons in the nine yielded these findings: (i) net output prices were 5 per cent or more higher; (ii) substantially fewer days of schooling were lost due to bad weather, largely because teachers had fewer absences; (iii) the acutely sick received more timely treatment and were more likely to be treated in a hospital than in the nearest primary health clinic; and (iv) the respondents ranked the resulting benefits in the domains of health and education at least as highly as the 'commercial' ones.